Risk-based models for potential large-scale landslide monitoring and management in Taiwan. Issue 2 (15th December 2017) - Lin, Chao-Yuan; Lin, Cheng-Yu; Chompuchan, Chuphan
ABSTRACT: Several related pre-event environment indices coupled with a 200-year event of Typhoon Morakot were used in this study to analyse landslide risk/scale for mapping and verifying the danger grade of watershed landslides. Risk analysis was modelled using maximum daily rainfall of the tested event as the hazard factor, and a complex indicator derived from indices of return period, road development and green deterioration as the vulnerability factor. The vulnerability factor was then modified using the slope to adjust the weight for excluding the flat areas and increasing impact of steep areas. A comprehensive indicator integrated from indices of river concave, headward erosion and dip slope was provided as the hotspot of potential large-scale landslides which were modified by vegetation index to correct sediment yield due to antecedent effects. Finally, sites with high potential large-scale landslide could be interpreted by the danger grade calculated from collapse risk/scale analysis. The results show that the higher the danger grade, the greater the collapse ratio; and the coefficient of determination for the relationship is greater than 0.9. The model developed in this study for accurately estimating the risk/scale of rainfall-induced landslide can be fulfilled.